PENGARUH MODEL INKUIRI TERBIMBING BERBANTUAN PHET SIMULATION TERHADAP PEMAHAMAN KONSEP IPA PESERTA DIDIK SD - Windy Aledya Rosyani; Nuraeni, Fitri; Fajrussalam, Hisny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low understanding of science concepts in Indonesia. The aim is to find out the effect of guided inquiry model assisted by PhET Simulation on the understanding of science concepts and the increase in understanding of science concepts of students who get guided inquiry model assisted by PhET Simulation compared to students who get cooperative model learning. The method used is quantitative quasi-experiment type and Nonequivalent Control Group Design, with a sample of IV A and IV C classes totaling 25 students each. Data were collected through test and non-test instruments. Tests in the form of multiple choice questions developed based on indicators of exemplifying, classifying, explaining, concluding. Non-test in the form of documentation, analyzed using descriptive and inferential data analysis. The results of data analysis showed that there was an effect of 48.4% of the guided inquiry model assisted by PhET Simulation on understanding the science concepts of elementary school students. Then there was an increase of 0.67 for the class with guided inquiry model learning assisted by PhET Simulation. While an increase of 0.41 for classes with cooperative learning models. The conclusion is that: 1) Guided Inquiry Model assisted by PhET Simulation in learning science affects the understanding of the concept of elementary school students; 2) The increase in understanding of science concepts of elementary school students who get the guided inquiry model assisted by PhET Simulation is better than students who get a cooperative learning model.